2021
DOI: 10.1097/grf.0000000000000652
|View full text |Cite
|
Sign up to set email alerts
|

In Utero Gene Therapy for Primary Immunodeficiencies

Abstract: Primary immunodeficiencies (PIDs) have become a prime target for gene therapy given the morbidity, mortality, and the single gene etiology. Given that outcomes are better the earlier gene therapy is implemented, it is possible that fetal gene therapy may be an important future direction for the treatment of PIDs. In this chapter, the current treatments available for several PIDs will be reviewed, as well as the history and current status of gene therapy for PIDs. The possibility of in utero gene therapy as a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 95 publications
0
3
0
Order By: Relevance
“…Regarding the treatment perspectives, it is noteworthy that many IEI monogenic diseases appear to be good candidates for gene therapy, e.g., X-linked SCID and X-linked GCD, ADA-SCID and Wiskott-Aldrich Syndrome, and several clinical trials have already been accomplished (107). The transition from engineered viral vectors to gene editing approaches, coupled with advances in hematopoietic stem cell transplantation, may bring new perspectives to this field of therapeutic research (17,107), Furthermore, the possibility of in utero gene therapy is already on our horizon (17).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the treatment perspectives, it is noteworthy that many IEI monogenic diseases appear to be good candidates for gene therapy, e.g., X-linked SCID and X-linked GCD, ADA-SCID and Wiskott-Aldrich Syndrome, and several clinical trials have already been accomplished (107). The transition from engineered viral vectors to gene editing approaches, coupled with advances in hematopoietic stem cell transplantation, may bring new perspectives to this field of therapeutic research (17,107), Furthermore, the possibility of in utero gene therapy is already on our horizon (17).…”
Section: Discussionmentioning
confidence: 99%
“…The majority of IEI present early in life, and a significant proportion of them, particularly the most severe ones, manifest in the first months of life, some even in the neonatal period (5)(6)(7)(8)(9)(10). Nevertheless, a few reports on intrauterine manifestations of IEI have been published, frequently represented by cases of hydrops fetalis in individuals in whom an IEI-related mutation was later identified in the family (7,9,(11)(12)(13)(14)(15)(16)(17). Commonly, infectious manifestations were the first and dominant features described in IEI patients but have not been reported in intrauterine life.…”
Section: Introductionmentioning
confidence: 99%
“…There are numerous reports showing that in utero therapies are becoming a reality for a multitude of conditions employing diverse modalities such as stem cell transplantation (e.g., BOOSTB4 for severe osteogenesis imperfecta type IV), intra-amniotic drug administration (e.g., ER004 for Xlinked hypohidrotic ectodermal dysplasia), in utero enzyme replacement therapy (IURET, e.g., for lysosomal storage diseases), and potentially, gene therapy and gene editing. 23 It has been demonstrated that in severely ill newborns, the sooner the treatment is initiated, the better the results. 21 What could be sooner than prenatal diagnosis?…”
Section: Patients Who Prefer Comprehensive Prenatal Detection Of As M...mentioning
confidence: 99%